Komodifikasi Agama dalam Budaya Islam Kontemporer: (Analisis Kritis terhadap Majelis Sabilu Taubah dalam Perspektif Theodore Adorno) - Muhammad Hanif Abdillah Widodo; Muhammad Hidayatur Ramadhan; Nadia Yasmine Mumtaz (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2025)
ABSTRACT This research analyzes the commodification of religion in contemporary Islamic culture through a case study of the use of DJ music at Gus Iqdam's recitation at Majelis Sabilu Taubah from the perspective of Theodor W. Adorno's Cultural Industry theory. The qualitative method of critical analysis is applied to primary (YouTube video recordings) and secondary data (online news, academic literature) to reveal the transformation of sacred values into consumption commodities. The findings show:(1) DJ music functions as a commodification strategy that packages religious rituals as popular entertainment products for market appeal and young audience reach;(2) This entertainment format reduces spiritual meaning through desacralizing the space of knowledge, shifting the focus of the congregation from religious contemplation to emotional sensation (Adorno's concept of cultural narcotics);(3) The practice reflects the submission of religion to the logic of the cultural industry-the reduction of transcendental value autonomy by instrumental rationality, creating false needs and blurring the sacred-profane boundary. This study contributes to the expansion of the Frankfurt School's critical theory in religious contexts while warning of the risk of silencing religious awareness and weakening the critical power of worshipers due to the industrialization of religious symbols. The implications emphasize the importance of preserving ritual integrity from market co-optation. Keywords : Cultural Narcotization, Pseudo-Individualization, False Needs